A new insight into the structure of Huolinhe lignite based on the yields of benzene carboxylic acids. (1st February 2017) - Yang, Fan; Hou, Yucui; Wu, Weize; Niu, Muge; Ren, Shuhang; Wang, Qian
Highlights: A new structural model of organic matter of Huolinhe lignite was constructed. The model had a molecular formula of C3942 H3666 O883 N50 S11 . The model explain the generation of BCAs in the process of lignite oxidation. The work provides a new way to study the organic matter structure of coal. Abstract: Coal is an important fossil energy. In order to improve its use efficiency, the study of its complex structure has drawn much attention all over the world. Since 1942, lots of molecular level models of coal have been proposed. However, they cannot reflect the yield distribution of benzene carboxylic acids (BCAs) that are generated from coal by oxidation. In this work, the organic matter structure of Huolinhe lignite was studied and a new structural model of organic matter of the lignite was constructed based on the yield distribution of BCAs from the oxidation of the lignite. Huolinhe lignite was analyzed via ultimate analysis, FTIR, XPS and 13 C NMR to investigate its elemental composition, organic functional groups, and carbons types and quantities. At first, various carbon structural parameters of the lignite were calculated through peak fitting of 13 C NMR. Then, combined with BCAs yields, aromatic clusters of the lignite model were built. Finally, a structural model of the lignite organic matter was constructed combined with the results of ultimate analysis, FTIR, XPS, 13 C NMR and the contents of carboxyl and phenolic hydroxyl groups. The results showed that the model had a molecular formula of C3942 H3666 O883 N50 S11, and a molecular weight of 66, 150 amu. The model can not only satisfy the results of ultimate analysis, FTIR, XPS, 13 C NMR and the contents of carboxyl and phenolic hydroxyl groups, but also explain the generation of BCAs in the process of lignite oxidation and satisfy the yield distributions of BCAs. The work provides a new way to study and construct the organic matter structural model of coal.